Computability theory and degree structures - Yuan, Bowen (Nanyang Technological University, 2020)
This thesis mainly studies the thin-free degrees. We show the technique to construct a thin-free degree, and construct a hyperimmune-free minimal thin-free degrees below 0'', and a nonbranching thin-free r.e. degree. We also show that any 1-generic degree below 0' is not thin-free, while any nonzero degree below a 2-generic degree is thin-free.